Conceptual Metaphors of Politics in Indonesian Online Mass Media: A Corpus-Based Analysis - Imam Musyayyab; Sailal Arimi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to examine the source domain of the target domain of POLITICS and the nuances of its meaning in Indonesian online mass media. It employs a qualitative research method to investigate the conceptual metaphors of POLITICS using a corpus-based approach. The data were obtained from 350 Indonesian online news articles that discuss politics over a period exceeding 13 months, starting from the election campaign period to the post-election period. The total number of tokens in the entire corpus amounted to 144,852. The corpus was analyzed using the AntConc tool (version 4.2.4) by utilizing the 5L & 5R collocate feature and KWIC. The Metaphorical Identification Procedure (MIP) was applied to analyze metaphors. The findings demonstrated the conceptual metaphors with negative connotations, namely POLITICS IS A TRANSACTION, and POLITICS IS A KINGDOM, and neutral connotations, namely POLITICS IS PHYSICAL SPACE, POLITICS IS A DRAMA SHOW, and POLITICS IS LOWLAND. However, conceptual metaphors with negative connotations were significantly more prevalent in linguistic expressions, suggesting that these metaphors more accurately reflect the political realities of Indonesia during the late 2023 to 2024 period.